EFEKTIVITAS PROGRAM USAHA EKONOMI PRODUKTIF KELOMPOK USAHA BERSAMA DALAM PEMBERDAYAAN MASYARAKAT MISKIN DI KABUPATEN BANJAR - Azki, Nuril (Jurnal Administrasi Publik dan Pembanguan, 2024)
The aim of this study; 1) Describe and analyze the effectiveness of the Joint Business Group Productive Economic Enterprises (UEP-KUBE) program in Empowering the Poor in Banjar District. 2) Analyze the inhibiting factors for the Effectiveness of the Joint Business Group Productive Economic Business Program (UEP-KUBE) in Banjar Regency. The research method uses a qualitative approach with a descriptive qualitative research type. Based on the results of research on the Effectiveness of the Joint Business Group Productive Economic Business Program (UEP-KUBE) in Empowering the Poor in Banjar Regency, in reality it can be said to be ineffective, because it has not fulfilled all indicators of effectiveness factors, namely Target Accuracy, Program Outreach, Program Objectives, Program Monitoring. The factors that become obstacles in the Effectiveness of the Joint Business Group Productive Economic Business Program in Empowering the Poor in Banjar Regency are based on the findings of researchers, such as 1) Culture, people tend to have individual characteristics, and do not want to work together in a group. 2) The technology used is still limited or inadequate. 3) The education of the recipient group is still low. 4) Poor social relations, this is because there is no cooperation in one group and each individual is competing to market the results obtained. 5) Economy, people use private funds to add feed. This causes the output to be greater than the input. 6) Natural Factors, is Floods hampered the implementation of the UEPKUBE program. Floods were experienced in several areas in Banjar Regency.  Keywords: Effectiveness, Joint Business Group Productive Economic Business Program